An in vitro approach to estimate putative inhibition of buprenorphine and norbuprenorphine glucuronidation - Oechsler, Stephanie; Skopp, Gisela (International journal of legal medicine, 2010)
An in vitro inhibition study was performed to investigate potential drug-drug interactions on glucuronidation of buprenorphine (BUP) and norbuprenorphine (NBUP), which represents the major elimination pathway of the drug using cDNA-expressed uridine 5′-diphosphate glucuronosyltransferases (UGTs) and human liver microsomes (HLMs). Following identification of major UGT enzymes for BUP and NBUP glucuronidation, substrates were incubated with drugs (amitriptyline, nortriptyline, lamotrigine, oxazepam, and temazepam), which are extensively cleared by glucuronidation as well as are often used during maintenance treatment. To evaluate the inhibitory potential, the half maximal inhibitor concentration (IC50), the inhibition constant (Ki), and the inhibitor concentration (KI) that yield half the maximum rate of inactivation and the enzyme inactivation rate constant (kinact) were determined, if appropriate. Amitriptyline and temazepam are inhibitors of NBUP glucuronidation (UGT1A3, HLMs), whereas BUP glucuronidation was affected by amitriptyline (HLMs), oxazepam, and temazepam (UGT2B7). Additionally, BUP inhibits NBUP glucuronidation (UGT1A1, 1A3, HLMs) and vice versa (UGT1A3). A decrease in the metabolic clearance of NBUP may increase the risk of adverse effects such as respiratory depression. Further investigations are needed to evaluate whether inhibition of BUP and NBUP glucuronidation contributes to adverse events.